Understanding What Makes Teaching Meaningful: A Systematic Literature Review of Antecedents and Determinants of Meaningful Work in Education - Olievia Prabandini Mulyana; Umi Anugerah Izzati; Jelita Citrawati Jihan; Yunia Dwie Nucahyanie; Meita Santi Budiani; Ni Wayan Sukmawati Puspitadewi; Dinda Cahya Novianti; Dinar Ester Marturia Oktaviana Simanjuntak (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Meaningful work is an essential aspect of teachers that can be influential in improving the quality of education; therefore, this study aimed to identify antecedent factors and determinants of meaningful work in teachers. Method: This study used a systematic literature review to examine the variables that can be antecedents and determinants of meaningful work. Results: Based on the literature studies that have been conducted, it is known that variables such as calling orientation, work role fit, workplace attachment, coworker relations, job design, altruistic behavior, authentic leadership, job crafting, and perceptions of organizational identification can be antecedent factors of meaningful work of teachers. Meaningful work can determine variables such as work attitude, teacher-student relationships, work engagement, burnout, resilience, self-rated health, intention to leave, corrosion at the character level, and organizational commitment. Novelty: This study thoroughly examines the antecedents and determinants of teachers' meaningful work variables, which, other yet to behave, need to be more widely researched.